Venturing into a quota-free world : the ready-made garment industry of Bangladesh - Razzaq, Abdur; Raihan, Selim (Dhaka : Pathak Shamabesh, 2008)
Contributed articles.
"South Asian Network on Economic Modeling."
Includes statistical tables.
Includes bibliographical references (p. [271]-274) and index.
Robin
Keywords: Clothing trade -- Bangladesh; Clothing trade -- Bangladesh -- Statistics; Export marketing -- Bangladesh; Bangladesh -- Commercial policy